THERMAL EQUATIONS OF STATE OF DIOCTAHEDRAL MICAS ON THE JOIN MUSCOVITE-PARAGONITE - Comodi P.; Gatta G.D.; Zanazzi P.F.; Levy D.; Crichton W. (My University, 2002)
Powder diffraction measurements at simultaneous high pressure and temperature on samples of 2M1 polytype of muscovite (Ms) and paragonite (Pg) were performed at the beamline ID30 of ESRF (Grenoble), using the Paris-Edinburgh cell. The bulk moduli of Ms, calculated from the least-squares fitting of V-P data on each isotherm using a second-order Birch-Murnaghan EoS, were: 57.0(6), 55.1(7), 51.1(7) and 48.9(5) GPa on the isotherms at 298, 573, 723 and 873 K, respectively. The value of (∂KT/∂T) was -0.0146(2) GPa K-1. The thermal expansion coefficient α varied from 35.7(3) × 10-6 K-1 at P ambient to 20.1(3) × 10-6 K-1 at P = 4 GPa [(∂α/∂P)T = -3.9(1) × 10-6 GPa-1 K-1]. The corresponding values for Pg on the isotherms at 298, 723 and 823 K were: bulk moduli 59.9(5), 55.7(6) and 53.8(7) GPa, (∂KT/∂T) -0.0109(1) GPa K-1. The thermal expansion coefficient α varied from 44.1(2) × 10-6 K-1 at P ambient to 32.5(2) × 10-6 K-1 at P = 4 GPa [(∂α/∂P)T= -2.9(1) × 10-6 GPa-1 K-1]. Thermoelastic coefficients showed that Pg is stiffer than Ms; Ms softens more rapidly than Pg upon heating; thermal expansion is greater and its variation with pressure is smaller in Pg than in Ms.
Keywords: MUSCOVITE; PARAGONITE; COMPRESSIBILITY; THERMAL EXPANSION; SYNCHROTRON POWDER DIFFRACTION